KORELAS I NILAI ABSORBAN Fe 2 + TERHADAP US IA BERCAK DARAH YANG DIANALI S I S DENGAN MENGGUNAKAN S PEKTROFOTOMETRI UV- Vi s - Misbahri "; M. Tegar Indrayana; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Bloodstains is one of the biological fluids are most commonly found onthe crime scene criminal cases. In the blood, there are 3 (three) components:erythrocytes, leukocytes, and plasma, iron (Fe) within the hemoglobin inerythrocytes can be utilized in the estimate of the age of bloodstain. At themoment the blood into blood, iron contained in hemoglobin (Fe2+) will reactwith the oxygen present in nature which will oxidize Fe2+ to Fe3+, The processof changing Fe2+ to Fe3+ can be used to estimate the age of bloodstain at thescene. One of them is by using UV-Vis spectrophotometry. This study aimed todetermine the correlation of absorbance (Å) Fe2+ to the age of bloodstain byusing UV-Vis spectrophotometry. This study is an experimental, Samples to beused as research is a white cotton cloth soaked in human blood. The resultsshow that no correlation was found from absorbance (Å) Fe2+ with the age ofbloodstain were analized using UV-Vis spectrophotometry.Keyword : Absorbance Fe2+, UV-Vis spectrophotometry, Bloodstain